Accessible Worship: The Receptivity of Religious Buildings in St. Louis - Vierkant, Katherine E.; Hollingsworth, Holly; Stark, Susan L. (Disability Studies Quarterly, 2006)
Although participation in organized religion provides many health and psychological benefits, fewer people with disabilities attend religious services than people without disabilities. Some models of disability suggest that one possible cause for this disparity may be the influence of environmental barriers in religious buildings. A random sample of 22 religious buildings in the St. Louis, Mo., metropolitan area was evaluated using the Community Health Environment Checklist to determine what environmental barriers a worshiper with mobility limitations might encounter when attending a worship service and using the restroom. The overall receptivity of participating congregations ranged from 46.7 to 92.1 out of 100, with lower scores indicating less receptivity than higher scores. The age of the building is positively correlated with the receptivity score (p < 0.05), indicating that older buildings are less likely to be receptive to people with mobility impairments. Over half of restrooms evaluated received scores indicating no receptivity. The results indicate that environmental barriers may be a significant barrier to religious participation by people with mobility impairments in some religious congregations. The findings of this study suggest that further examination of the impact of the environment on religious participation by people with disabilities is warranted.